Influence of Light Conditions and Light Sources on Clinical Measurement of Natural Teeth Color using VITA Easyshade Advance 4.0® Spectrophotometer: Pilot Study - Ivona Posavec; Vladimir Prpić; Dubravka KNEZOVIĆ ZLATARIĆ (University of Zagreb. School of Dental Medicine, 2016)
Objectives: The purpose of this study was to evaluate and compare lightness (L), chroma (C) and hue (h), green-red (a) and blue-yellow (b) character of the color of maxillary right central incisors in different light conditions and light sources. Materials and methods: Two examiners who were well trained in digital color evaluation participated in the research. Intraclass correlation coefficients (ICCs) were used to analyze intra- and interobserver reliability. The LCh and L*a*b* values were determined at 08.15 and at 10.00 in the morning under three different light conditions. Tooth color was assessed in 10 subjects using intraoral spectrophotometer VITA Easyshade Advance 4.0® set at the central region of the vestibular surface of the measured tooth. Results: Intra- and interobserver ICC values were high for both examiners and ranged from 0.57 to 0.99. Statistically significant differences in LCh and L*a*b* values measured in different time of the day and certain light condition were not found (p>0.05). Statistically significant differences in LCh and L*a*b* values measured under three different light conditions were not found, too (p>0.05). Conclusions: VITA Easyshade Advance 4.0® is reliable enough for daily clinical work in order to assess tooth color during the fabrication of esthetic appliances because it is not dependent on light conditions and light sources.